Determinan Kualitas Laporan Keuangan: Studi pada Lembaga Pendidikan Tinggi Negeri Vokasi di Jawa Timur - Aristia Indah Dewishabrina; Endro Sugiartono; Ika Ristianingsih (Politeknik Negeri Jember, 2021)
This study aims to analyze and explain the effect of human resource competence, the use of information technology, and the application of government accounting standards on the quality of the financial statements of vocational higher education institutions in East Java. This study uses quantitative methods with research instruments using questionnaires. The data analysis technique used is multiple linear regression analysis with the application of IBM SPSS Statistics 22. The results of this study indicate that the competence of human resources, the use of information technology, and the application of government accounting standards have a significant positive effect on the quality of the financial statements of vocational higher education institutions in East Java.